1996
DOI: 10.1159/000237310
|View full text |Cite
|
Sign up to set email alerts
|

Cetirizine Exerts Anti-Inflammatory Effects on Human Neutrophils

Abstract: Leukotrienes are potent lipid mediators involved in acute and chronic inflammatory processes and allergic inflammation. Cetirizine is an H1-receptor antagonist used in the treatment of allergic symptoms. We analyzed the effect of cetirizine on the formation of leukotriene B4 (LTB4) after stimulation of human peripheral blood neutrophils. The inflammatory mediators were analyzed after cellular activation with different stimuli: the Ca ionophore A23187, which bypasses membranous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…In particular, cetirizine can facilitate proton transfer, a property of biological relevance [29] [30]. ± This study confirms the importance of conformational effects on the partition properties of cetirizine and hydroxyzine, with obvious pharmacokinetic implications.…”
Section: Resultssupporting
confidence: 70%
“…In particular, cetirizine can facilitate proton transfer, a property of biological relevance [29] [30]. ± This study confirms the importance of conformational effects on the partition properties of cetirizine and hydroxyzine, with obvious pharmacokinetic implications.…”
Section: Resultssupporting
confidence: 70%
“…Nevertheless, other antirelease activities of this drug were described more recently, using other cells and other mediators, and more importantly, physiological concentrations in vitro (±0.5 µ M ). Such concentrations of the drug inhibited the release of toxic products from atopic platelets [17]and eosinophils [18]and the release of LTB 4 from human neutrophils [19]. These in vitro data were confirmed in several in vivo conditions in atopic subjects.…”
Section: The Inhibition Of Mediator Releasementioning
confidence: 81%
“…Clinical studies of children demonstrated that cetirizine also possesses anti-inflammatory activity; it reduces production of leukotrienes in vitro [7,11]. Effect of the leukotriene level decrease is caused by the decreased migration of leukotriene-producing cells (eosinophils, basophils, and macrophages) towards the allergic response site [12].…”
Section: Pharmokokineticsmentioning
confidence: 99%